The medical ethics curriculum in medical schools: present and future - Giubilini, A; Milnes, S; Savulescu, J (University of Chicago Press, 2016)
In this review paper we describe the current scope, methods and contents of medical ethics education in medical schools in Western English speaking countries (mainly the UK, the US, and Australia). We assess strengths and weaknesses of current medical ethics curricula, also in light of students’ levels of satisfaction with different teaching approaches and their reported difficulties in learning medical ethics concepts and applying them in clinical practice. We identify 3 main challenges of medical ethics education: counteracting the bad effects of the “hidden curriculum”; teaching students how to apply ethical knowledge and critical thinking to real cases in clinical practice; shaping future doctors’ right character through ethics education. We suggest ways in which these challenges could be addressed. On the basis of this analysis, we propose practical guidelines for designing, implementing, teaching and assessing a medical ethics program within a 4 year Medical course.